Spatial Differentiation of the Land and Nutrient Footprints for Kampala: Implications for Urban Food Sustainability - Joyfred Asaba; Paul Isolo Mukwaya; Shauib Lwasa; Yazidhi Bamutaze; Fredrick Omolo (Forum Geografi)
Rapid urban growth, together with an increase in urban food demand and rural-urban food flows, effectively transfer the urban footprint to the surrounding cities. In Uganda, where fast urban growth is evident, data on the resultant foodprint is sparse. To bridge this gap in knowledge, this paper quantitatively analyses the flows of the rural-urban cooking banana (matooke) to Kampala, Uganda, and the embedded land and nutrient footprints. Food freight surveys involving interviews with food truck drivers and field measurements were used to obtain data on quantities of banana flow to ten purposively sampled city markets. The results confirm that 88.5% of Kampala’s banana inflows are sourced from the Ankole sub-region. Disaggregation of the flows by season revealed a 52% fall in banana supplies to the city during the wet season. The calculated annual land footprint associated with the city’s banana inflows was 15,268 hectares. The hot spots for NPK nutrient mining are in the Ankole region, including mean daily losses of 362.29±29.13Kg (K), 104.66±8.42Kg (N) and 4.03±0.32Kg(P). The ANOVA results exhibited significant differences (P˂0.05) in the cooking banana land and nutrient footprints between the source regions and concerning the dry and wet seasons, except for the Rwenzori, Kigezi, and Bunyoro sub-regions pertaining to the land footprint and Buganda, Tooro, and  Bunyoro as regards the nutrient footprint. These results emphasise the intense rural nutrient mining that is associated with urban food consumption. Thus, to guarantee sustainable matooke production, there is a need to establish waste diversion strategies that enable nutrient recycling back to rural farms.